2012
DOI: 10.1016/j.bbadis.2012.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress increases BACE1 protein levels through activation of the PKR-eIF2α pathway

Abstract: Beta-site APP cleaving enzyme 1 (BACE1) is the rate limiting enzyme for accumulation of amyloid β (Aβ)-peptide in the brain in Alzheimer's disease (AD). Oxidative stress (OS) that leads to metabolic dysfunction and apoptosis of neurons in AD enhances BACE1 expression and activity. The activation of c-jun N-terminal kinase (JNK) pathway was proposed to explain the BACE1 mRNA increase under OS. However, little is known about the translational control of BACE1 in OS. Recently, a post-transcriptional increase of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
139
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(148 citation statements)
references
References 76 publications
9
139
0
Order By: Relevance
“…This possibility has been demonstrated in Alzheimer disease mouse models and Alzheimer disease brains. 28 The phosphorylation of eIF2a by kinases, including PKR, leads to an inhibition of protein synthesis, as seen in an Alzheimer disease mouse model, 37,38 except for proteins with a peculiar reading frame that are putatively implicated in stress-response signalling pathways, such as BACE1. 39 Our result is in agreement with that of a previous work showing an increase of JNK3 activity in Alzheimer disease brains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This possibility has been demonstrated in Alzheimer disease mouse models and Alzheimer disease brains. 28 The phosphorylation of eIF2a by kinases, including PKR, leads to an inhibition of protein synthesis, as seen in an Alzheimer disease mouse model, 37,38 except for proteins with a peculiar reading frame that are putatively implicated in stress-response signalling pathways, such as BACE1. 39 Our result is in agreement with that of a previous work showing an increase of JNK3 activity in Alzheimer disease brains.…”
Section: Discussionmentioning
confidence: 99%
“…We used 30 μg of the supernatant for immunoblot analysis, as previously described. 28 Bound proteins were visualized with the Odyssey Imaging System (Li-COR Biosciences) and quantified with MultiGauge software (Fuji). Assays were performed in duplicate.…”
Section: Human Brain Immunoblottingmentioning
confidence: 99%
“…A link between Alzheimer’s disease (AD) and reduced global translation was established in 1989, when Langstrom et al demonstrated that polysomes from the cortices of AD patients were associated with less RNA than those from controls. Subsequently, increased levels of p-eIF2α were found in the cortex and hippocampus of AD patients and in AD mouse models (Chang et al, 2002b; Devi and Ohno, 2013; Hoozemans et al, 2009; Kim et al, 2007; Lewerenz and Maher, 2009; Ma et al, 2013; Mouton-Liger et al, 2012; O’Connor et al, 2008; Page et al, 2006; Stutzbach et al, 2013; Unterberger et al, 2006). In addition to AD, p-eIF2α levels are elevated in the brain or spinal cord of patients and mice with prion disease (Unterberger et al, 2006), amyotrophic lateral sclerosis (ALS; Ilieva et al, 2007), Parkinson’s disease (PD; Hoozemans et al, 2007, 2012), Huntington’s disease (HD; Leitman et al, 2014), and various tauopathies (Köhler et al, 2014; Nijholt et al, 2012; Radford et al, 2015; Stutzbach et al, 2013; Unterberger et al, 2006).…”
Section: Neurodegenerative Diseases Associated With Dysregulation Ofmentioning
confidence: 99%
“…Analysis of the phosphorylated form of PKR and/or PERK (p-PKR, p-PERK) in patient brains demonstrated increased activation of these kinases in various neurodegenerative diseases (Bando et al, 2005; Nijholt et al, 2012; Stutzbach et al, 2013). For example, elevated p-PKR and p-PERK is observed in the AD brain, particularly in the hippocampus and cortex, regions associated with Aβ plaques and neurofibrillary tangles (Chang et al, 2002a; Hoozemans et al, 2009; Ma et al, 2013; Mouton-Liger et al, 2012; Onuki et al, 2004; Peel and Bredesen, 2003; Unterberger et al, 2006). p-PKR and p-PERK are also increased in the brains of patients with prion disease (Paquet et al, 2009; Unterberger et al, 2006) and PD (Bando et al, 2005; Hoozemans et al, 2007, 2012).…”
Section: Neurodegenerative Diseases Associated With Dysregulation Ofmentioning
confidence: 99%
“…Similar to BACE1, ATF4 mRNA contains multiple upstream open reading frames in its 5 0 UTR, which act to suppress translation under basal conditions, but undergo scan-through after phosphorylation of eIF2a, leading to selective translational up-regulation during conditions of ER stress. 36,65,69 ATF4 subsequently translocates to the nucleus to up-regulate the expression of genes involved in the UPR. Thus, we determined whether ATF4 was increased in the nucleus of ritonavir-treated neuroglial cultures after 16 hours of treatment.…”
Section: Ritonavir Up-regulates Bace1 Expression In a Translation-depmentioning
confidence: 99%